Comparative evaluation of rural electrification project plans: A case study in Mexico. (June 2019) - Gómez-Hernández, D.F.; Domenech, B.; Moreira, J.; Farrera, N.; López-González, A.; Ferrer-Martí, L.
Abstract: Rural electrification project plans (REPP) aim to expand electricity access through adequate systems for communities without this service in developing countries. Many REPP have been developed, using different strategies in terms of energy uses covered, energy resources, electricity distribution and management models. This paper aims to analyze and compare REPP strategies. To do so, an evaluation methodology is developed, using a novel three-level assessment approach: the general definition at regional scale, the technical design at local scale, and the operation and maintenance (O&M) management. More specifically, ad hoc criteria are defined at each level to examine REPP fulfilment through quantitative and qualitative indicators. As case study, three plans from Chiapas (Mexico) are evaluated: national grid extension with national O&M; individual photovoltaic systems with regional O&M; and wind-photovoltaic microgrids with local O&M. Thus, the strengths and limitations of each REPP are identified in terms of strategies at regional scale, local scale and management model. Results show the ability of large plans to provide electricity to many families, while small plans may be adapted to the specific needs of end-users. The proposed criteria and indicators can be easily adjusted to evaluate REPP in different contexts to strengthen future plan strategies. Highlights: Rural electrification project plan strategies from Chiapas (Mexico) are evaluated. national grid extension; (2) individual PV systems; (3) wind-PV microgrids. A 3-level assessment is used: regional scale, technical design and management model. Evaluation criteria/indicators are proposed and can be adjusted to different contexts. Large plans supply many families, while small ones directly respond to end-users.